Collaborative governance and communication models to build religious harmony - Mustofa, Amirul (Jurnal Studi Komunikasi, 2022)
This study aims to analyse the harmony of religious communities with religious leaders through a collaborative governance perspective supported by the communication model. This research uses a qualitative research approach. I collected data through documents, interviews, and observations—analysing data by interactive model analysis. The results of this study are various kinds of friction between religious communities and religious leaders, which can be resolved by building a good relationship as unique culture (silaturahmi). Silaturahmi agrees that stakeholders institutionalised as a new model in solving religious harmony. Collaboration between religious leaders is committed to assisting community needs through social assistance and providing recommendations for places of worship. On the other hand, a collaboration between stakeholders requires a face-to-face, dialogical, and mass communication model.